2015
DOI: 10.1016/j.jcis.2015.02.025
|View full text |Cite|
|
Sign up to set email alerts
|

Physical mechanisms of interaction of cold plasma with polymer surfaces

Abstract: Physical mechanisms of the interaction of cold plasmas with organic surfaces are discussed. Trapping of plasma ions by the CH 2 groups of polymer surfaces resulting in their electrical charging is treated. Polyethylene surfaces were exposed to the cold radiofrequency air plasma for different intervals of time. The change in the wettability of these surfaces was registered. The experimentally established characteristic time scales of the interaction of cold plasma with polymer surfaces are inversely proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Unfortunately, the detailed mechanisms of hydrophilization and hydrophobic recovery remain unclear . In our recent papers we have demonstrated that plasma treatment charges polymer films electrically; in doing so the characteristic times of hydrophobic recovery and surface charge loss are close …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the detailed mechanisms of hydrophilization and hydrophobic recovery remain unclear . In our recent papers we have demonstrated that plasma treatment charges polymer films electrically; in doing so the characteristic times of hydrophobic recovery and surface charge loss are close …”
Section: Introductionmentioning
confidence: 99%
“…Appearance of polar groups on the polymer surface leads to a change in wetting behavior, thus, strengthening the hydrophilicity of treated materials [23]. However, the surface roughness is also affected by the plasma treatment that can also change its wettability [20,24]. Surface properties of plasma treated polymers depend on, e.g., gases composition, exposure time, frequency and plasma power [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the reorientation of the polar groups into the bulk polymer and the second is the mobility of small polymer chain segments into the matrix [10]. Thus, the results of these processes are a decrease in surface energy and a significant decrease of surface wettability [8,10,12,13,24].…”
Section: Introductionmentioning
confidence: 99%
“…One of those is hightemperature plasma, and generally produced by a plasma torch. 11) Here, electrons and atoms realize thermal equilibrium having little difference in their temperatures. To pro-duce such state, high electric energies are required.…”
Section: Fly Ashmentioning
confidence: 99%